OBSERVATIONS ON THE MULLET FISHERY IN THE HOOGHLY AND MAHANADI ESTUARINE SYSTEMS - Thakur, Nirmal K (Indian Journal of Fisheries, 2011)
Trends of mullet fishery have been studied on the basis of recorded data from the Hooghly estuary (1959-66) and the Mahanadi estuary (1962-64). The size structure of different speciet in the catches and the fluctuations therein have been examined. Areas of fishing and fishing,methods have been described. Attempts have been made to correlate the fluctuations of landings of tlifferent species with certain environmental features.